HORMONAL PROFILE AND HELPFUL RESULTS REPRODUCTIVE TECHNOLOGIES IN FEMALE PATIENTSWITH DIFFERENT FORMS OF STERILITY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Target:To evaluate the hormonal profile and identify the determinants that determine the effectiveness of the extracorporeal fertilization program (ЕКО) in patients with various etiological infertility.Materials and Methods: Retrospectively analyzed data of 301 women who passed cycles of ЕКО/ИКСИ in 2021–2025. The concentrations of prolactin, thyrotropin hormone (ТТГ), follicle stimulating hormone (FSH), luteinizing hormone (ЛГ), estradiol, progesterone and antimullerova hormone (АМГ) are investigated. Statistical processing included descriptive statistics, Student's t-test and Pearson correlation analysis. Statistical significance was established at p < 0,05.
Keywords: Infertility, auxiliary reproductive technologies, hormonal profile, antimuller hormone, SPKIA, fertility.